THE IMPORTANCE OF INCENTIVENESS IN THE DEVELOPMENT OF STUDENT ACTIVITIES IN THE HIGHER EDUCATION SYSTEM - Yuldasheva Malohat Erkinovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the importance of motivation in the development of cognitive activity of students of pedagogical universities and its positive features and the role of the educator in the educational process. The article addresses issues such as cognitive interest and the emergence of cognitive processes.